Not all screens are created equal: examination of surface features and other physical properties of commonly used screen materials for smoking drugs - Bradley J. Diak; Miroslav Miskovic; Nadia Zurba; Denise Beaumont (BMC, 2023)
Abstract Background Brass screens are considered an essential part of the safer drug smoking/inhalation supplies and are widely distributed by harm reduction programs in Canada. However, the use of commercially available steel wools as screens for smoking crack cocaine remains a common practice among people who smoke drugs in Canada. Use of these steel wool materials is associated with different adverse effects on health. This study aims to determine what changes folding and heating have on several filter materials, including brass screens and commercially available steel wool products, and examine the implications of these changes on health of people who smoke drugs. Methods This study investigated the microscopic differences, studied by optical and scanning electron microscopy, between four screen and four steel wool filter materials used in a simulated drug consumption process. New materials were manipulated, compacted into its own Pyrex® straight stem using a push stick and then heated with a butane lighter simulating a common method in preparing drugs for consumption. The materials were studied in the as-received (new), as-pressed (compressed and inserted into the stem tube but without heating) and as-heated (compressed and inserted into the stem tube and heated with a butane lighter) conditions. Results The steel wool materials with the smallest wire thicknesses were found to be the easiest to prepare for pipe use, but degrade significantly during shaping and heating, making them wholly unsuitable as a safe filter material. In contrast the brass and stainless steel screen materials remain mostly unchanged by the simulated drug consumption process. After the stainless steel pellet screen, the Brass Impact 2.0 screen material had the best characteristics of the materials tested due to its mesh wire diameter, pitch, alloy choice and its pre-strained state. Conclusion Commonly used steel wool alternatives degrade during the handling and stem insertion, and heating the screens in the stem. Debris is generated by wool deformation on insertion and after heating that easily separates from the screen and can be inhaled during drug consumption. The brass and stainless steel screen materials are safer to use as they remain mostly stable during the simulated drug consumption process.